Temperature Trajectory Subphenotypes Correlate With Immune Responses in Patients With Sepsis. Issue 11 (November 2020) - Bhavani, Sivasubramanium V.; Wolfe, Krysta S.; Hrusch, Cara L.; Greenberg, Jared A.; Krishack, Paulette A.; Lin, Julie; Lecompte-Osorio, Paola; Carey, Kyle A.; Kress, John P.; Coopersmith, Craig M.; Sperling, Anne I.; Verhoef, Philip A.; et al.
Abstract : Objectives: We recently found that distinct body temperature trajectories of infected patients correlated with survival. Understanding the relationship between the temperature trajectories and the host immune response to infection could allow us to immunophenotype patients at the bedside using temperature. The objective was to identify whether temperature trajectories have consistent associations with specific cytokine responses in two distinct cohorts of infected patients. Design: Prospective observational study. Setting: Large academic medical center between 2013 and 2019. Subjects: Two cohorts of infected patients: 1) patients in the ICU with septic shock and 2) hospitalized patients with Staphylococcus aureus bacteremia. Interventions: Clinical data (including body temperature) and plasma cytokine concentrations were measured. Patients were classified into four temperature trajectory subphenotypes using their temperature measurements in the first 72 hours from the onset of infection. Log-transformed cytokine levels were standardized to the mean and compared with the subphenotypes in both cohorts. Measurements and Main Results: The cohorts consisted of 120 patients with septic shock (cohort 1) and 88 patients with S. aureus bacteremia (cohort 2). Patients from both cohorts were classified into one of four previously validated temperature subphenotypes: "hyperthermic, slow resolvers" ( n = 19 cohort 1; n = 13 cohort 2), "hyperthermic, fast resolvers" ( n = 18 C1; n = 24 C2), "normothermic" ( n = 54 C1; n = 31 C2), and "hypothermic" ( n = 29 C1; n = 20 C2). Both "hyperthermic, slow resolvers" and "hyperthermic, fast resolvers" had high levels of G-CSF, CCL2, and interleukin-10 compared with the "hypothermic" group when controlling for cohort and timing of cytokine measurement ( p < 0.05). In contrast to the "hyperthermic, slow resolvers, " the "hyperthermic, fast resolvers" showed significant decreases in the levels of several cytokines over a 24-hour period, including interleukin-1RA, interleukin-6, interleukin-8, G-CSF, and M-CSF ( p < 0.001). Conclusions: Temperature trajectory subphenotypes are associated with consistent cytokine profiles in two distinct cohorts of infected patients. These subphenotypes could play a role in the bedside identification of cytokine profiles in patients with sepsis. Abstract : Supplemental Digital Content is available in the text.